The third angel a novel - Hoffman, Alice 1952- (Shaye Areheart Books, 2008)
Charts the lives of three London women, each in love with the wrong man. Meanwhile, a fourth woman spends decades searching for the Third Angel-- the angel on earth who will renew her faith
Keywords: Faith / Fiction; Angels / Fiction; Angels -- Fiction; Faith -- Fiction; London (England) / Fiction; London (England) -- Fiction; Psychological fiction; Love stories